La comunicación y su influencia en la vida cotidiana. estudio de uso y abuso del smartphone - Manjarrez Gaibor, Marlon Ariel (2025)
Communication is important in everyday life because it enables the exchange of ideas, emotions, and information in a variety of contexts. In the digital age, smartphones have become a vital tool that has transformed the way people interact. This study examines the impact of smartphone use and abuse on the dynamics of communication, highlighting both the benefits and associated problems. Advantages include accessibility, immediacy, and global connectivity; however, excessive use can have negative consequences such as dependency, decreased face-to-face communication, and social isolation. Surveys and observations were used to identify usage patterns that reflect how the smartphone influences productivity, interpersonal relationships, and mental health. The study found that while technology can facilitate communication, abuse can lead to stress, insomnia, and loss of concentration on vital tasks. This analysis invites reflection on the importance of balanced use, promoting responsible practices that reap the benefits without jeopardizing the quality of human interaction.